A strategic analysis of Saudia using the PEG framework - Aquilina-Spagnol, Clive; Ellis, Darren (Cranfield University, 2021)
This paper conducts a strategic analysis of Saudia using a recent strategic framework of analysis developed specifically for air transport; that is, the politics, economics and geography (PEG) framework. The motivation to analyse Saudia stems from the ongoing doctoral research the lead author is currently carrying out which is focused on investigating the strategic trajectories of the Middle East big three (MEB3). In this study Saudia has been identified as a potential key competitor which can exert pressure on the future trajectories of the traditional big three Gulf carriers, Emirates, Etihad and Qatar. Given PEG is a novel framework developed specifically for the airline industry, and is simple and straight forward to use, it is considered a ‘best fit’ for Saudia, particularly when primary data about the airline is yet to be collected. Saudia is also heavily influenced by geopolitics. The analysis in this paper is structured based firstly on the category of politics, then geography and finally economics. The outcome of the first two categories demonstrates the extent to which politics and geography are more important to the airline than economics, as far as strategic direction is concerned. They also reveal that the airline may even enjoy better fundamentals than the MEB3 and, given the new economic vision of the Kingdom, the possibility of overshadowing one of the MEB3 is not excluded in the medium term. Porter’s five forces of competition strategic framework of analysis was also used when analysing Saudia, particularly in relation to the PEG category of economics. It is recommended that a PEG analysis of Saudia is supported by further analysis through other strategic frameworks to better uncover key factors and forces shaping the airline’s strategic future.
Keywords: PEG; MEB3; Saudia; strategic analysis; geopolitics